WHY TIME MANAGEMENT MATTERS MOST IN TODAY’S FAST-PACED WORLD, ESPECIALLY FOR TEENAGERS - Sevinch Rakhimkulova Azimjonovna, (TADQIQOTLAR, 2026)
ANNOTATION:  This  article  explores  the  growing  importance  of  time management in modern society, focusing particularly on teenagers who face academic pressure, digital distractions, social expectations, and future career planning. It explains why managing time effectively is not just a productivity skill but a life skill that shapes discipline,  mental  health,  success,  and  personal  growth.  Without  setting  clear boundaries and sticking to a well-rounded plan, it is hard to climb the career ladder while  simultaneously  allocating  time  meaningfully.  Through  real-life  examples, practical explanations, and research-supported insights, the article demonstrates how mastering time management early can transform teenagers into confident, organized, and goal-oriented individuals.